UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL MIND MAP - Yanti Nazmai Ekaputri; Melni Rosari (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This title was raised because researchers realized in managing classroom learning, especially in science learning that had not used a learning model that was centered on students, this situation had an impact on students who did not look enthusiastic during learning so that student learning outcomes were low or did not meet the Minimum Mastery Criteria ( KKM). The main issues in this study are: Efforts to improve the activities and learning outcomes of Natural Sciences; teacher ability and student activity in each cycle; and student learning outcomes in each cycle. One effort to overcome these problems is to use the mind map model. Mind map model is a learning model that is a way to obtain, store, and access information or learning material obtained by students processed by the brains of students. This model is a way of learning using pictures, symbols and colors that are very liked by children so that students are active and interested and motivated in following the lessons. Learning that can stimulate students to be more active and creative can improve student learning outcomes.The purpose of this study is: To find out how to improve the ability of teachers and activities of students in learning science by using the Mind Map model in class V MIN 7 Pessel, To find out how to improve learning outcomes of science by using the Mind Map model in class V MIN 7 Pessel. This type of research is a classroom action research (CAR) with the subject of the research being the students of class V MIN 7 Pessel totaling 17 people. The type of data used in this study is qualitative and quantitative data. Data analysis techniques used are the analysis of teacher ability, analysis of student activities, and analysis of student learning outcomes. The techniques and instruments of this study are tests and observations.The results showed an increase in the ability of teachers to manage learning in each cycle. Cycle I am 71.15% (enough), cycle II increased by 82.69% (good) and cycle III increased to 98.07% (very good). While the results of research on student activity in the learning process also showed an increase in each cycle, the percentage results in cycle I were 57.14% (less), cycle II 82.14% (good), and cycle III 96.42% (very good). Student learning outcomes through the application of mind mapping method in the initial test was 29.41% in the first cycle increased by 52.94%, the second cycle 82.35%, and the third cycle 94.11% and the final test increased to 100%. Thus, it can be concluded that the use of mind map models can improve learning outcomes of students in class V MIN 7 Pessel